Study of therapeutic response to vincristine in patients with refractory primary immune thrombocytopenia (ITP) - حسين فراس (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Immune thrombocytopenic purpura (ITP), also known as idiopathic thrombocytopenic purpura, is an autoimmune disorder in which platelets are destroyed by the immune system as a result of unknown immune triggers. Treatment of primary immune thrombocytopenia (ITP) is often chronic and difficult. The use of corticoids and/or splenectomy is associated with a cure in 70-90% of cases. Vincristine is often effective in treating refractory primary immune thrombocytopenia (ITP). It is characterized by its rapid action and its mechanism of action linked to immunosuppression of macrophages, inhibiting the production of antiplatelet antibodies, and stimulating the production of platelets from the bone marrow. Aim of study : Determine the therapeutic response to vincristine treatment in the fourth week of treatment in patients with essential immune thrombocytopenic purpura refractory to corticosteroids in splenectomised and non-splenectomised patients and studying the continuation of the response for one year after the end of vincristine infusion and thus determine the effect of splenectomy before vincristine treatment on the therapeutic response. Sample and research methods: The study sample included 30 patients with primary immune thrombocytopenic purpura (ITP) refractory to corticoids, 12 patients who had a splenectomy, and 18 patients without a splenectomy. The study was conducted in the Hematology Department at Tishreen University Hospital in Lattakia during the time period 2017-2020. The study criteria included adult patients greater than or equal to 18 years of age with previously diagnosed ITP after ruling out secondary causes, isolated thrombocytopenia less than 20,000/ml with or without bleeding symptoms at the start of the study, normal liver function, without previously known immune disease, without contraindication to the use of treatment with vincristine or its contraindications, negative serology for viral hepatitis, refractory to corticosteroid treatment with prednisolone, solimedrol, or high doses of dexamethasone, with or without splenectomy. Patients’ consent was obtained for admission. A form was prepared for each patient, and all patients were given a complete blood count (CBC), liver and kidney functions, serum CRP to rule out infections, and screening for viral liver markers. Vincristine was given at a dose of 2 mg as an intravenous infusion over two hours, weekly for four weeks, then vincristine treatment was stopped. Platelet numbers were assessed before the infusion began in the first week, then weekly for four weeks, then every 3 months for a year, and the results of platelet numbers were recorded in the patients’ forms. Results: 1- An increase in platelet count starting from the first week of treatment compared to the value pre- treatment, and the increase continued clearly and significantly until the fourth week of treatment, with statistically significant differences, but the increase was higher in the group of splenectomized patients after the third and fourth week. 2- High incidence of partial and complete response in the third and fourth weeks among splenectomized patients (100% of patients), as complete response occurred in a quarter of patients (25%) in the third week and in more than half of the patients (58.3%) in the fourth week . In contrast , low rate response in non-splenectomized patients (partial and complete response in only 55.5% of patients), as no therapeutic response was recorded at all in the first and second weeks in 100% of patients. A partial response occurred in the third and fourth weeks, while a complete response occurred only in 11.1% in the fourth week. Therefore, this study leads us to the fact that patients with thrombocytopenic purpura refractory to glucocorticoids and splenectomy are the group who most benefit from vincristine treatment. 3- An increase in platelet counts in the follow-up at 3, 6, 9, and 12 months of treatment compared to the value pre- treatment, with statistically significant differences. platelet numbers begin to decrease gradually, but the values were significantly lower at 3 and 6 months of treatment in the group of non-splenectomized patients. 4- Continued response to treatment is observed in( 91.7%) of the splenectomized patients compared to (27.8%) in the group of non-splenectomized patients after 12 months of treatment. Non-continuation of the therapeutic response in (72.2%) in the group of non-splenectomized patients compared to( 8.3%). ) in the group of splenectomized patients after 12 months of treatment. Conclusion: Immune thrombocytopenic purpura refractory to glucocorticoids and splenectomy responds well to vincristine treatment, with the response continuing for 12 months after stopping treatment in more than 90% of patients.